Learning to read in Williams syndrome and Down syndrome: syndrome-specific precursors and developmental trajectories. - Steele, A; Scerif, G; Cornish, K; Karmiloff-Smith, A (2013)
BACKGROUND: In typical development, early reading is underpinned by language skills, like vocabulary and phonological awareness (PA), as well as taught skills like letter knowledge. Less is understood about how early reading develops in children with neurodevelopmental disorders who display specific profiles of linguistic strengths and weaknesses, such as Down syndrome (DS) and Williams syndrome (WS). METHODS: Early reading, letter knowledge, rhyme matching, phoneme matching and receptive vocabulary were assessed in 26 children with DS and 26 children with WS between 4 and 8 years, as well as in two groups of typically developing (TD) children matched on nonverbal mental age (NVMA controls) or reading (RA controls). Reading was also measured 1 year later in DS, WS and RA controls to assess reading growth and its longitudinal predictors. RESULTS: Despite poor PA and vocabulary, children with DS displayed good reading and letter knowledge, compared with NVMA controls. Performance of children with WS was equivalent to RA controls and superior to NVMA controls on all tasks. Longitudinal delays emerged in reading in both DS and WS compared with RA controls. Vocabulary was a significant longitudinal predictor of reading growth for all children, but, for both children with DS and WS, and unlike RA controls, letter knowledge and PA were not. CONCLUSIONS: Children with DS and WS display atypical developmental patterns in the earliest stages of reading, further underlining the importance of cross-syndrome, longitudinal research, which tracks all levels of development in neurodevelopmental disorders. Identifying early syndrome-specific profiles of strengths and weaknesses underlying literacy development is critical for planning intervention programmes.